ChemInform Abstract: Enantio‐ and Diastereoselective Hetero‐Diels—Alder Reactions Between 4‐Methyl‐substituted Rawal′s Diene and Aldehydes Catalyzed by Chiral Dirhodium(II) Carboxamidates: Catalytic Asymmetric Synthesis of (‐)‐cis‐Aerangis Lactone (XII). Issue 26 (1st July 2014) - Watanabe, Yudai; Shimada, Naoyuki; Anada, Masahiro; Hashimoto, Shunichi
Abstract High yields and high enantioselectivities are achieved when DMAD and acetyl chloride are used in the workup of the hetero‐Diels‐Alder reaction.